2019
DOI: 10.1016/j.buildenv.2019.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Transient human thermophysiological and comfort responses indoors after simulated summer commutes

Abstract: The current study investigates the transient human physiological and comfort responses during sedentary activity following a period of elevated activity in a hot condition. Such metabolic and thermal down-steps are common in buildings as occupants arrive after commuting in summer. It creates a serious problem for thermostatic control, since arriving occupants find their transition uncomfortably warm at temperatures that resident occupants find comfortable. Fifty-nine participants (29 men, 30 women) dressed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 30 publications
3
15
1
Order By: Relevance
“…It has also been found that a modest air speed significantly reduces a CO2 bubble that accumulates in a person's breathing zone under still air conditions in workstations [16]. Finally, higher air temperatures and air speeds have also recently been shown to be far more effective (compared to cooler temperatures and still-air) at restoring comfort to occupants who have just entered a space with elevated metabolic rate and stored body heat from walking [17,18]. Note that in each of these above cases the desirable air flows are isothermal, involving only the room air itself.…”
Section: Comfort Zones and Air Quality Effects Under Elevated Air Movmentioning
confidence: 99%
“…It has also been found that a modest air speed significantly reduces a CO2 bubble that accumulates in a person's breathing zone under still air conditions in workstations [16]. Finally, higher air temperatures and air speeds have also recently been shown to be far more effective (compared to cooler temperatures and still-air) at restoring comfort to occupants who have just entered a space with elevated metabolic rate and stored body heat from walking [17,18]. Note that in each of these above cases the desirable air flows are isothermal, involving only the room air itself.…”
Section: Comfort Zones and Air Quality Effects Under Elevated Air Movmentioning
confidence: 99%
“…Our previous study [3] found that although the metabolic level, heart rate, and skin blood flow were able to recover in a few minutes after the exercise and ambient temperature stepdown, the core temperature remained elevated during the entire 60 min. Further measurement of these longer-term heat storage changes after commutes would be useful in projecting occupants' thermal requirements over periods as long as a day.…”
Section: Discussionmentioning
confidence: 91%
“…Especially in warm weather, such increases affect people's thermal comfort well after they have entered cooler air-conditioned indoor spaces and become sedentary. Thermal sensation, comfort, and physiological responses all require time to reach steadystate indoor values [3], primarily due to body heat that was stored during the exercise in the heat [4,5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surprisingly they are not usually turned on until the period 10:30 to 12 noon (Fig. 7b), rather than around 9am upon arrival, this is probably related to the higher metabolic rate that occupants experience during their commute, and the time required for body heat to dissipate [25]. Like the windows, there are large differences in usage frequency between the different heaters ( Fig.…”
Section: Heatersmentioning
confidence: 97%